(untitled) (Research, Society and Development, 2020)
Classical Literature has been confined to academic spaces, apart from that, it is no longer a component of the Basic Education curriculum in the country. Such features concern us since reading classic works can be considered a useful way to expand the cultural repertoire, the worldview, and oneself. Access to literature, as argued by Candido is a basic right, and it is important that we develop means to democratize it. Therefore, we seek to develop a literary literacy proposal for Elementary and Secondary Education, based on the assumptions of Cosson, through the basic and expanded sequences. Moreover, we ground our discussion on Machado, Calvino, Candido, Paulino, among others. This proposal, therefore, favors reflection on the relevance of classical literature for the formation of the young subject-reader while offering an alternative to his teaching.